Study The Pathological Changes Resulting From Copper Deficiency In Awassi Sheep Organs: Jenan A.Al-Khalide , Saade Ahmed khanawe , Lela M.zake - Al-Khalide, Jenan A. (The Iraqi Journal of Veterinary Medicine, 2007)
To induce copper deficiency in sheep (15)Awasi ewes from the college ofVeterinary Medicine flock were used. The ewes during the preparationperiod (18 weeks) were fed on balanced concentrated diet contained (5.2)mg/day copper in addition of the green food.The ewes were randomly divided into three equal groups for theexperimental period (18 weeks). Another balanced concentrated diet with lowlevel of copper (2.6) mg/day was used to feed the primary deficiency groupwhile the secondary copper deficiency group fed on the same concentrate used inthe preparation period. The protein ratio and energy level were considered.The secondary deficiency group received an oral mixture of ammoniummolybdate (100) mg with (1) g of sodium sulphate in (100) ml of water daily.One ewe and two lambs died from the primary deficiency group however adead still born lamb was born from the secondary deficiency group. Thepostmortem examination of dead animals studies was done and histopathologicalsamples from the central nervous system, heart, lung, kidney and muscles wereexamined.The histopathological examination showed vaculation, degeneration withdemylination in central nervous system. These changes were more sever inlumber and thoracic than cervical spinal cord. The same changes were found inthe cerebrum and cerebellum. While the liver, heart, lung, kidney showedhydropic degeneration and cloudy swelling. The symptoms and changes throughthe experimental period were more obvious in the secondary deficiency groupthan in the primary one.